Extraction of lipids from Yarrowia Lipolytica - Milanesio, Juan Manuel (2013)
Microorganisms have often been considered for the production of oils and fats as an alternative to agricultural and animal resources. Extraction experiments were performed using a strain of the yeast Yarrowia lipolytica (Y. lipolytica), a high‐lipid‐content yeast. Three different methods were tested: Soxhlet extraction, accelerated solvent extraction (ASE) and supercritical carbon dioxide (SCCO2) extraction using ethanol as a co‐solvent. Also, high pressure solubility measurements in the systems ‘CO2 + yeast oil’ and ‘CO2 + ethanol + yeast oil’ were carried out.